2020
DOI: 10.1177/8755122520911689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety and Efficacy of Metformin Use in Hospitalized, Non–Critically Ill Patients

Abstract: Background: Contraindications and precautions to metformin have limited inpatient use, and limited evidence exists evaluating metformin in hospitalized patients. Objective: This study aimed to determine the safety and efficacy of inpatient metformin use. Methods: This study was an observational, retrospective, cohort study at an academic medical center between June 1, 2016, and May 31, 2018. Hospitalized adults with type 2 diabetes mellitus receiving at least 1 metformin dose were included. The primary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One cohort study found no difference in serious adverse events, but it was likely not powered to detect rare outcomes. 15 The present study did not specifically evaluate differences in safety events but does demonstrate that inpatient use of metformin is relatively prevalent in hospitalized patients. Although previous studies were primarily randomized controlled trials and the present study is a cohort study, this study provides additional information on inpatient diabetes management not answered by previous studies.…”
Section: Discussionmentioning
confidence: 81%
“…One cohort study found no difference in serious adverse events, but it was likely not powered to detect rare outcomes. 15 The present study did not specifically evaluate differences in safety events but does demonstrate that inpatient use of metformin is relatively prevalent in hospitalized patients. Although previous studies were primarily randomized controlled trials and the present study is a cohort study, this study provides additional information on inpatient diabetes management not answered by previous studies.…”
Section: Discussionmentioning
confidence: 81%